Comprehensive Physiology 1996
DOI: 10.1002/cphy.cp120122
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Exercise on Protein and Amino Acid Metabolism

Abstract: The sections in this article are: General Aspects of Amino Acid and Protein Metabolism in Muscle Amino Acid Transport and the Free Amino Acid Pool Outline of the Metabolism of Amino Acids in Muscle in Relation to Exercise Interrelationship of BCAA , Alanine, and Glutamine Metabolism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(72 citation statements)
references
References 237 publications
0
68
1
Order By: Relevance
“…As described above, protein and amino acid breakdown is promoted during exercise. It has been confirmed that muscle protein synthesis increases during the resting recovery period after exercise 4,41) , and that this increased protein synthesis lasts for at least 2 days after exercise 41,42) . This suggests that nutrient intake after exercise should effectively increase protein synthesis.…”
Section: Regulation Of Protein Metabolism By Leucinementioning
confidence: 85%
See 4 more Smart Citations
“…As described above, protein and amino acid breakdown is promoted during exercise. It has been confirmed that muscle protein synthesis increases during the resting recovery period after exercise 4,41) , and that this increased protein synthesis lasts for at least 2 days after exercise 41,42) . This suggests that nutrient intake after exercise should effectively increase protein synthesis.…”
Section: Regulation Of Protein Metabolism By Leucinementioning
confidence: 85%
“…Furthermore, muscle contains 3-5 g of free amino acids, which play an active role in protein metabolism 4,5) . Therefore, proteins and amino acids are very important nutrients to sustain or increase skeletal muscle mass in humans.…”
Section: Protein and Amino Acid Metabolism In Skeletal Musclesmentioning
confidence: 99%
See 3 more Smart Citations